Alternative to antibiotic growth promoters: beneficial effects of Saccharomyces cerevisiae and/or Lactobacillus acidophilus supplementation on the growth performance and sustainability of broilers’ production - Attia, Youssef A.; Basiouni, Shereen; Abdulsalam, Nisreen M.; Bovera, Fulvia; Aboshok, Afaf A.; Shehata, Awad A.; Hafez, Hafez M. (Frontiers in Veterinary Science, 2023)
Although antibiotics growth promoters (AGPs), including zinc-bacitracin (ZnB), can threaten human health due to developing antimicrobial resistance, as well as drug residue in animal and poultry products, ZnB is still widely used, particularly in developing countries, for the sustainability of poultry farming. The present investigation aims to assess the use of Saccharomyces cerevisiae and Lactobacillus acidophilus, with or without a prebiotic (mannooligosaccharide, MOS), as alternatives to ZnB. For this reason, 150 one-day-old chicks were grouped into six groups, designated negative control, LA, SC, ZnB, SA+MOS, and LA+MOS (5 replicates of 5 chicks for each group). Chicks kept in the control group were fed the basal diet. Chickens kept in LA and SC groups received L. acidophilus, S. cerevisiae at a 1g/kg diet and 2 g/Kg, respectively. Chickens kept in ZnB received ZnB at 0.5 g/kg. Chicks kept in the SC+MOS and LA+MOS were fed a basal diet containing 2 g S. cerevisiae + 1g MOS/kg or 1g L. acidophilus +1 g MOS /kg, respectively. The efficacy was assessed based on the growth performance, carcass traits, meat quality, nutrient digestibility, and blood biochemistry composition during the entire trial 1-36 days of age. Results showed that chicks kept in the SC group had greater BW than the control (P<0.05). Chicks kept in the SC, LA, SC+MOS, and LA+MOS consumed less feed than the control and Zn-B groups (P<0.05). Supplementation with S. cerevisiae resulted in a better (P<0.05) feed conversion rate (FCR) than the control group. Supplementation with L. acidophilus +MOS significantly increased (P<0.05) the relative liver weight compared to those supplemented with ZnB, S. cerevisiae, and L. acidophilus. In addition, supplementation with ZnB-induced spleen hypertrophy compared to S. cerevisiae and L. acidophilus-supplemented groups (P<0.05). Plasma, meat, and liver cholesterol, as well as the cholesterol-to-lipid ratio of meat and liver, were significantly decreased (P<0.05) in both SC and LA groups compared to the control group. Our research indicates that adding 2 g/kg of S. cerevisiae to broiler feed can effectively replace ZnB and enhance productive performance and economic profits, making it a viable and sustainable option for broiler farming.